Not the End of the World - Atkinson, Kate (TRANSWORLD PUBLISHERS, 2015)
Not the End of the World is Kate Atkinson's first collection of short stories. Playful and profound, they explore the world we think we know whilst offering a vision of another world which lurks just beneath the surface of our consciousness, a world where the myths we have banished from our lives are starrlingly present and where imagination has the power to transform reality. From Charlene and Trudi, obsessivle making lists while bombs explode softly in streets outside, to gormless Eddie, maniacal cataloguer of fish, and Meredith Zane who may just have discovered the secret to eternal life, each of these stories shows that when the worlds of material existence and imaginations collide, anything is possible.